Da'wah for Social Justice: Creating Awareness of Social Issues Through a Religious Approach - Karimullah, Suud Sarim; Said, Nurhidayat Muhammad; Rahmah, St.; Wasalmi, Wasalmi; Syafi’i, Achmad Ghozali (Jurnal Dakwah Risalah, 2023)
This study analyzes the critical role of da'wah in building social awareness, encouraging concrete actions, and empowerment in achieving social justice through a religious approach. The literature research method with a literature analysis review is used in this study as an approach that focuses on extracting, reviewing, and evaluating various literature sources that are relevant to the topic of study. The study's findings stated that da'wah is integral in advancing social awareness, encouraging concrete actions, and forming continuity in the struggle to achieve social justice through a religious approach. With a system based on spiritual values, da'wah can potentially change society's paradigm toward social issues. However, to achieve significant results, da'wah must be seen as an integral component in broader social efforts, focusing on partnerships, local understanding, and patience in overcoming challenges.